REBT Counseling Approach in Overcoming for The Trauma of Children Victims of Domestic Violence - Rahmad Firmansyah; Netrawati; Zadrian Ardi; Pu’ad Maulana; Thessia Permata Bunda (Journal Of Psychology, Counseling And Education, 2025)
This article discusses how to implement the REBT counseling approach to overcome the trauma of child victims of domestic violence. Trauma can be said to be a psychological symptom that can cause children to be afraid as a result of the events they experience and cause the child to imagine events that make them afraid, anxious, anxious or psychologically disturbed so that they need help to overcome it. One of the REBT counseling approaches is an approach whose application can rationalize children's thoughts that were previously irrational to become rational. Counseling with the REBT approach as one methode to overcome the trauma of child victims of domestic violence which includes discussions such as Trauma, what is domestic violence, the REBT approach, the role of the counselor and the implementation of the REBT approach to overcome trauma in child victims of domestic violence in counseling.